Inverse curvature flows in hyperbolic space - Gerhardt, Claus (Journal of differential geometry, 2011)
We consider inverse curvature ows in Hn+1 with star-shaped initial hypersurfaces and prove that the ows exist for all time, and that the leaves converge to infinity, become strongly convex exponentially fast and also more and more totally umbilic. After an appropriate rescaling the leaves converge in C∞ to a sphere.
Gesehen am 08.11.2023